Molecular dynamics simulation on CH4 combustion in CO2/O2/N2 atmosphere subjected to electric field. Issue 8 (24th May 2023) - Zhou, Junjie; Sun, Zhaochen; Tang, Songzhen; Yu, Yinsheng
ABSTRACT: In this paper, the CH4 combustion characteristics in CO2 /O2 /N2 atmosphere subjected to electric field were studied by the molecular dynamics simulation method. Conventional and unique pathways were obtained. The evolution law of reactants and main products and the first reaction time of main intermediates under the influence of different electric field intensities were analysed. Results showed that the addition of external electric fields increased conventional responses and species diversity. The generation of new pathways induced the production of new species, and the further reactions of new species produced other new pathways, thus accelerating the generation of new pathways and species in the electric field. It was noteworthy that, the applied external electric field could advance the reaction start time and reinforce the combustion process, but its effect on the reaction rate was highly nonlinear. The CH4 reaction with CO2 was significantly intensified at E  ≥ 10 5 V/m, while suppressed at E  = 10 4 V/m. Furthermore, electric fields could promote the oxidation degree of CH4, especially at E = 10 6 V/m. The studies provide theoretical guidance for revealing the mechanism of methane combustion under a high concentration CO2 atmosphere and promoting the efficient capture of CO2 .